Vegetation Recovery in Slash‐Pile Scars Following Conifer Removal in a Grassland‐Restoration Experiment. Issue 6 (14th July 2014) - Halpern, Charles B.; Antos, Joseph A.; Beckman, Liam M.
Abstract A principal challenge to restoring tree‐invaded grasslands is the removal of woody biomass. Burning of slash piles to reduce woody residues from forest restoration practices generates intense, prolonged heating, with adverse effects on soils and vegetation. In this study, we examined vegetation responses to pile burning following tree removal from conifer‐invaded grasslands of the Oregon Cascades. We quantified the longevity and magnitude of fire effects by comparing ground conditions and the cover and richness of plant species in burn‐scar centers (higher‐intensity fire) and edges (lower‐intensity fire) with adjacent unburned vegetation 7 years after treatment. We interpreted patterns of recovery through the responses of species with differing growth forms, habitat affinities, and clonality. Cover of bare ground remained elevated at the centers, but not at the edges of scars; however, much of this effect was due to gopher disturbance. Total plant cover, consisting entirely of native species, was comparable in and adjacent to scars. However, richness remained depressed at the scar centers. Cover of grass, meadow, and non‐clonal species was comparable in and adjacent to scars, but cover of forb, sedge, residual forest, and clonal species was reduced at the centers. Although scar centers had a simpler community structure (fewer but more abundant species) than the adjacent vegetation, they remained free of exotics and recovered quickly, aided by the soil‐disturbing activities of gophers and the regenerative traits of native, disturbance‐adapted species. Pile burning can be a viable and efficient approach to fuel reduction in the absence of exotics.